Star cluster formation in Orion A. (25th May 2020) - Lim, Wanggi; Nakamura, Fumitaka; Wu, Benjamin; Bisbas, Thomas G; Tan, Jonathan C; Chambers, Edward; Bally, John; Kong, Shuo; McGehee, Peregrine; Lis, Dariusz C; Ossenkopf-Okada, Volker; Sánchez-Monge, Álvaro
Abstract: We introduce new analysis methods for studying the star cluster formation processes in Orion A, especially examining the scenario of a cloud–cloud collision. We utilize the CARMA–NRO Orion survey 13 CO (1–0) data to compare molecular gas to the properties of young stellar objects from the SDSS III IN-SYNC survey. We show that the increase of v_^13CO - v_YSO and Σ scatter of older YSOs can be signals of cloud–cloud collision. SOFIA-upGREAT 158 μm [C ii ] archival data toward the northern part of Orion A are also compared to the 13 CO data to test whether the position and velocity offsets between the emission from these two transitions resemble those predicted by a cloud–cloud collision model. We find that the northern part of Orion A, including regions ONC-OMC-1, OMC-2, OMC-3, and OMC-4, shows qualitative agreements with the cloud–cloud collision scenario, while in one of the southern regions, NGC 1999, there is no indication of such a process in causing the birth of new stars. On the other hand, another southern cluster, L 1641 N, shows slight tendencies of cloud–cloud collision. Overall, our results support the cloud–cloud collision process as being an important mechanism for star cluster formation in Orion A.